De consumidor a leitor: veredas à formação leitora - Martino, Simone Rodrigues (2018)
The research presented in this dissertation aims to investigate if it is possible to initiate the process of literary literacy with middle school students working with the narrative of Harry Potter and the Sorcerer’s Stone, by J. K. Rowling (2000). We noticed, through our practical observation in the classroom and our professional experience, how young learners showed typical reading behavior when in contact with literary books classified as contemporary young adult, such as Harry Potter – a literary phenomenon that sold more than 400 million copies around the world and changed the publishing market. For this reason, we considered that it would be relevant to elaborate a reading action proposal that included the students’ enthusiasm towards those books, but that could also take them to the pathways of literary reading, leading them, at some point of their reading paths, aiming the reading of masterpieces of literature. We also reflected about the way literary reading has been developed in schools and the opposition that takes place in teaching institutions between the tradition – which determines the reading of the canonized classics – and the mediatized and marketed universe in which the young readers live nowadays, for which the non-canonized books prevail. Besides, to enlarge the range of interest in the narrative reading among teenage students, we proposed the production of a fanfiction – genre that has a large penetration in the universe of young people, because in a fanfiction they can modify a story whatever they like and also, they can see it been read and commented by their peers – based on the narrative of Harry Potter and the Sorcerer’s Stone. We elaborated and executed an intervention project in a 7th grade class of a public state middle school in Cascavel, in the state of Paraná, in 2017, in the form of workshops divided in 4 modules, with a varied quantity of classes, that depended on the themes and the rhythm of development of the students. This project was based on a bibliographic review about the themes on teaching and learning literary reading in school, and on the theorical contributions of the action-research methodology. We counted on the theorical assumptions of Colomer (2003; 2007;2017); Petit (2008); Lajolo (1984); Martins (2000); the DCEs of Paraná Stated (2008); Soares (2011); Sodré (1988); Jauss (1994) and Zilberman (2009) to support our work and the analysis of the development of application we performed and about the literature, the reception and the way it is practiced in school. We were also supported by the premises of Candido (1972; 2011) to endorse the importance of the literature and its humanizing role. Jamison (2017) helped us to discuss fanfictions. Supporting our intervention proposal are the theorical assumptions of the Reception Theory, by Jauss (1994), Iser (1979) and Aguiar and Bordini (1993). Analyzing the question of the literary readers formation in school, we performed a bibliographic-qualitative approach, which practices are supported by the assumptions of the action-research. We consider that the teaching professionals, so anguished by the problems with the formation of literary readers, cannot prescind from the possibility to add to their practices in the classroom books and narratives that might stimulate the curiosity of their students for reading them. This way, they can initiate their young learners in the process of reading formation. We hope that this research can contribute with the pathways of literary reading in school